Acoustic characteristics of voice in examinees with moderately-severe hearing loss - Slađana Ćalasan; Nadica Jovanović-Simić; Snežana Babac; Mirjana Petrović-Lazić (Биомедицинска истраживања, 2019)
Introduction: Voice is the result of vocal cord vibrations and resonance effects of the vocal tract, therefore, the instrumental monitoring of the vibrations themselves is one of the essential aspects of objective instrumental assessment of voice. Inadequate height and volume, as well as increased nasality, represent the basic characteristics of voice in hearing-impaired persons. The aim of the study was to perform a detailed analysis of the acoustic structure of vowel /a/ in the hearing-impaired persons and in those with normal hearing and voice. Methods: The sample comprised 40 participants, aged 17 to 20 years (18.50 ±1.13), both sexes (50% males), divided into two groups. The first group consisted of 20 participants with moderately-severe hearing loss (56-70 dB), while the second group included 20 normal-hearing participants. Members of both groups were equal to each other in sex and age (± 3 months). The research was conducted in secondary schools, the Faculty of Medicine in Foča, as well as in Special School with a Student's Dormitory "Bubanj" in Niš during May 2018. Results: A statistically significant difference between hearing-impaired and normal-hearing speakers was found in 11 out of 14 tested acoustic parameters of vowel /a/: Standard Deviation of Fundamental Frequency (STD), Absolute Jitter (Jitta), Percentage of Jitter (Jitt), Relative Average Perturbation (RAP), Fundamental Frequency Variation (vFo), Shimmer (Shdb), Percentage of Shimmer (Shim), Amplitude Perturbation Quotient (APQ), Noise-to-Harmonic Ratio (NHR), Soft Phonation Index (SPI) and Frequency Tremor Intensity Index (FTRI) whereby the hearing-impaired participants showed higher values of the above-mentioned parameters. Conclusion: The obtained results show pathological changes in the voice of hearing-impaired persons, as well as the need for voice rehabilitation.
Keywords: voice disorders; acoustic voice analysis; moderately-severe hearing loss